COMPARATIVE STUDY ON THE CORROSION OF ALLOYS IN ARTIFICIAL SALIVA - Laurenţiu Drăguş; Cosmin Mihai Cotruţ; Alexandru Daniel Referendaru; Raluca Monica Comăneanu; Doina Lucia Ghergic (Amaltea Medical Publishing House, 2018)
Four types of dental alloys used in metal-ceramic technology, two NiCr-based and two CoCr-based, were studied for corrosion resistance. Of the 4 types of alloys, circular samples of 14 mm in diameter and 4 mm thickness were poured into the dental laboratory which were subsequently processed and subjected to corrosion in artificial saliva at the temperature of the human body (37 ± 0.5°C) and at pH = 5.2. In corrosion resistance testing performed, one of the CoCr-based alloys was shown to have the lowest corrosion current density, the lowest corrosion rate and a high polarization resistance.